Meningkatkan Motorik Halus Peserta Didik Disabilitas Intelektual Melalui Permainan Lego di SLB Negeri 1 Kubung - Tiarahman, Rizki Agus; Taufan, Johandri; Efrina, Elsa; Mahdi, Arisul; Zulpiani, Mardhatillah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the improvement of fine motor skills in students with intellectual disabilities through Lego play. The research method used is single subject research with an A-B design conducted over 10 meetings, consisting of 3 meetings of the baseline phase (A1) and 7 meetings of the intervention phase (B). The research subject is a student with intellectual disabilities at SLB Negeri 1 Kubung. The data obtained is analyzed descriptively quantitatively. The results showed that in the baseline phase (A1) the student's fine motor skills were stable at a mean level of 55% with a stability range of 8.25%, while in the intervention phase (B) there was a significant gradual increase with a mean level of 77.71% and a stability range of 12.6%. Data analysis showed a significant increase of 22.71% from the baseline phase to the intervention phase. The tendency of the data trace changed from flat in the baseline phase to increasing in the intervention phase. Overlap data of 0% indicates no overlap between the two phases, indicating a very strong intervention effectiveness with a stability percentage that remains at 85.7% which indicates a consistent and controlled ability improvement process